The OECD at work - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1964)
This publication covers: OECD Aims and working Methods; Economic Policies and Trends; The Flow of Financial Resources to the Developing Countries; Technical Co-operation with the Developing Countries; The OECD Development Centre; International Trade; Invisible Trade; Manpower and Social Affairs; Industry and Energy; Agriculture; Fisheries; The Contribution of Science and Education to Economic Growth; The European Nuclear Energy Agency; OECD Links with other International Organizations; OECD publications
rpm 28/11/2017
Loans
Keywords: Economic Co-operation and Development; Organisation for Economic Co-operation and Development